Penegakan Hukum Kepolisian Polres Ternate dalam Menanggulangi Peredaran Minuman Keras pada Masyarakat Kota Ternate - Gunawan Hi Abbas; Paulus Tri Arso (Universitas Muhammadiyah Purwokerto, 2021)
The concrete legal problem that becomes the problem in the city of Ternate is that the center of the supply of liquor (miras) is very high from various centers of Halmahera which are imported by sea, so that it makes it a bit difficult for the police to detect it, this should get serious attention from the city government of Ternate to deal with the problem. liquor which is widely consumed by the wider community, even traded in free places, ironically again among the younger generation, students, who can get it in a freely accessible place. In fact, the influence on the attitudes and actions of perpetrators of these alcohol users is very high, such as speeding on the highway which can disrupt traffic, create noise and chaos, and disturb the peace of other communities. This is due to reduced self-control due to excessive drinking. Various calls for the local government of the city of Ternate to pay more attention to the rampant distribution of liquor, of course there are signals from several sides, both in terms of legislation, regional regulations, which are implemented, law enforcement officials, and the legal culture of the community. Thus questioning law enforcement means positioning law enforcers in the context of realizing the objectives of law with security and order for the realization of a peaceful and prosperous society through an organization. The regional government together with the Ternate City DPRD to be asked to immediately revise the Regional Regulation (Perda) of Ternate City Number 5 of 2004 concerning alcohol which is considered not able to cause a deterrent effect, because the penalties regulated in the existing Ternate municipal regional regulations stipulate the maximum penalty, should be able to replaced with minimal penalties so as to have a deterrent effect on liquor sellers and users.Keywords: Law Enforcement, Alcoholic Beverage